Percutaneous Transhepatic Fontan-Kreutzer Completion of Hepatic Vein Inclusion. Issue 6 (November 2018) - Juaneda, Ignacio; Peirone, Alejandro; Ferrero Guadagnoli, Adolfo; Contreras, Alejandro; Orozco, Santiago; Diaz, Juan; Kreutzer, Christian
We report the case of an 11-year-old girl with heterotaxy syndrome, dextrocardia, and azygos continuation of an interrupted inferior vena cava who had developed pulmonary arteriovenous fistulas after a Kawashima procedure consisting of bilateral superior cavopulmonary anastomoses. She presented with profound cyanosis, fatigue, and failure to thrive. An operative procedure to direct hepatic vein effluent to the pulmonary circulation was performed with placement of an extracardiac conduit between the hepatic veins and the left pulmonary artery. Persistence of cyanosis led to investigation, which led to the discovery of an unintentionally excluded right hepatic vein. A percutaneous transhepatic catheter intervention was performed in which a vascular plug was implanted to occlude the "missed" right hepatic vein, redirecting the flow through intrahepatic venovenous channels to the conduit. Clinical condition and arterial oxygen saturation were substantially improved one year after the two-step hepatic vein inclusion procedure.